O pensamento francês na geografia rural do Brasil - Flamarion Dutra Alves (Confins)
This article aims to discuss the theoretical-methodological developments of the Brazilian agrarian geography, starting in 1939. Through the analysis of selected scientific geography journals, it is possible to demonstrate the predominance of French lablachian tradition in rural studies published between 1939 and 1970. Thus, the re-reading of works originating from classical Brazilian agrarian geography contribute to theoretical and methodological reflections on the history of thought, as well as assists in discussions about the theoretical-methodological approaches used in recent researches.